2017
DOI: 10.1287/moor.2016.0835
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Deferred-Acceptance Auctions

Abstract: Deferred-acceptance auctions are mechanisms whose allocation rule can be implemented using an adaptive reverse greedy algorithm. Milgrom and Segal recently introduced these auctions and proved that they satisfy remarkable incentive guarantees: in addition to being dominant strategy and incentive compatible, they are weakly group-strategyproof and can be implemented by ascending-clock auctions. Neither forward greedy mechanisms nor the VCG mechanism generally possess any of these additional incentive properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 44 publications
0
39
2
Order By: Relevance
“…Dütting et al [11] showed that, even in the binary setting, if the set of bidders that can be simultaneously accepted is defined by a single knapsack constraint of size m, then no DA auction can achieve an approximation better than O(log m). The following theorem provides a matching positive result: a generalized DA auction that achieves the optimal logarithmic approximation.…”
Section: Deferred-acceptance Auctions For Multiple Levels Of Service mentioning
confidence: 99%
See 2 more Smart Citations
“…Dütting et al [11] showed that, even in the binary setting, if the set of bidders that can be simultaneously accepted is defined by a single knapsack constraint of size m, then no DA auction can achieve an approximation better than O(log m). The following theorem provides a matching positive result: a generalized DA auction that achieves the optimal logarithmic approximation.…”
Section: Deferred-acceptance Auctions For Multiple Levels Of Service mentioning
confidence: 99%
“…Backward greedy algorithms can be inferior to forward greedy algorithms, and the former need not even produce an inclusion-maximal solution. Driven by this concern, Dütting et al [11] subsequently explored the power and limitations of DA auctions from an approximation algorithms viewpoint (see also related work below). Their main results concern knapsack auctions and combinatorial auctions with single-minded bidders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally, the trade-off may also involve the type of incentive compatibility condition that we want. For example, [6] showed that a certain class of weakly group strategyproof mechanisms (studied in [14]) can only achieve an approximate social welfare in binary one-parameter domains.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
“…Proof. We first prove that the particular tie-breaking rule of the mechanism satisfies the following condition: 6 For any i and j = i the following implication holds…”
Section: C5 Proof Of Theorem 19mentioning
confidence: 99%